(untitled) (Malaysian Management Journal, 1992)
This paper investigates the effects of acquisition’s announcement on the stock prices of the acquiring firms, around the announcement dates. Announcements made during the period 1983 to 1987 were included in this study. The results shows that there is no significant difference in the price change of the acquiring firms during the period, as compared to other firms in the market.